Infrastructures of intimacy - Susanna Paasonen (Routledge, 2025)
What was two decades ago a special, knowing and ultimately rare added layer of communication in the form of mundane social arrangements made through email, webcam sessions, newsgroup exchanges or internet relay chat (IRC), exchanges in and through networked media have, especially with the ubiquity of social media services and the mobile internet, become elementary components of social communication. Connections are constantly made, maintained and severed in Tinder matches, flirtatious Facebook interactions, sexual Snapchat sessions, Skype conversations, vitriolic Twitter exchanges and confessional WhatsApp messages.
Mediated Intimacies: Connectivities, Relationalities and Proximities